Use of Real-Time Quantitative PCR To Detect Chlamydophila felis Infection - Helps, Chris (American Society for Microbiology, 2001)
A real-time PCR assay was developed to detect and quantify Chlamydophila felis infection of cats. The assay uses a molecular beacon to specifically identify the major outer membrane protein gene, is highly reproducible, and is able to detect fewer than 10 genomic copies.